Changing the Landscape of the City Outskirts. Bon Pastor (Barcelona) - Remesar, Antoni; Vergel, Javier; Barreiro, Augusta; Chávez, Tatiana; Chaves, Laura (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2022)
The paper presents the territorial and axiological context and the peculiarities of the participatory project developed by the Polis Research Centre and the Bon Pastor Neighbourhood Association, as well as the first steps in the design of two interventions. The first intervention, the Wall and Party Walls in Rodriguez de la Fuente Square, is proposed within the framework of the sustainable development strategies of Barcelona City Council. Its main objective is to achieve thermal insulation of the affected dwellings, thus contributing to the well being of the residents and to the reduction of CO2 emissions into the atmosphere. Besides, it is aimed to solve landscape discontinuity. In the lower part of the party walls, there is a wall, a kind of plinth that the residents have chosen as a site for the expansion of the work on the civic remembrance of the neighbourhood. There, the “Living Memory” space will be set up, reserved for interventions by children from the quarter’s schools through a work programme run in cooperation with them. The second intervention is the case of the centennial Mulberry Tree classified as a tree of local interest. In 2018, the mulberry tree suffered some damage from thugs who threw firecrackers inside. Therefore, the need was pointed out to reorganise the space around the tree in order to create dissuasive effects and preserve its integrity. These are preliminary studies to be discussed by the agents involved in the project: the Sant Andreu District, the IMPUQV (Institut Municipal del Paisatge Urbài la Qualitat de Vida), and the Bon Pastor Neighbourhood Association.